Carbon Stocks Potential of Peatland Forests Typologies in Central Kalimantan - Muhammad Abdul Qirom; Tri Wira Yuwati; Purwanto Budi Santosa; Wawan Halwany; Dony Rachmanadi (Jurnal Ilmu Kehutanan)
Accuracy of carbon stocks estimation can be enhanced by measuring each carbon pools in various forest peatland typologies. The carbon stocks measurement is associated with the amount of contents and fractions of carbon stocks. The research objectives were to obtain the information of carbon contents and carbon stocks potentials in each carbon pool in the peat typologies. Carbon stocks measurement was conducted in five carbon pools which were: vegetation (tree stages), litter, understory, necromass, and soil. The results showed that the carbon contents reached more than 50% of its dry weight. The carbon contents were not affected by the carbon pools and peat typologies. In the soil carbon pools, peat depth affected the amount of carbon content so that the magnitude of the conversion factor should concentrate to the depth of each peat typology. The greatest potential of carbon stocks was found in the secondary forest (3,733.08 Mg/ha) with the peat depths between 3-3.5 m, while the lowest potential of carbon stocks found in the bush typology (2243.49 Mg/ha) with the peat depths between 3-3.5 m. In the peat typology, soil carbon stocks contributed more than 95% of total carbon stocks whereas necromass carbon stocks contributed the smallest amount of carbon. The fractions of carbon stocks in each carbon pools were soil> vegetation> litter> understorey> necromass, respectively.